Awareness of diabetic foot disease among patients with diabetes mellitus in Al-Ahsa Saudi Arabia - Aldhafar, Abdulaziz S.; Abdalla, Mohamed; Althafar, Abdulaziz K. (International Surgery Journal, 2021)
Background: The prevalence of diabetes mellitus (DM) in Saudi Arabia is 18.3% in 2020. One of the most common complications that affects diabetic patients is diabetic foot disease (DFD). Patient education is the most effective way to reduce the complications of DFD. Methods: A cross-sectional study was conducted in the period from January to May 2021. A pretested standardized questionnaire was used to collect information upon knowledge, attitude and practice toward diabetic foot care. Data entry was performed using SPSS. Results: The responses of 480 of which 294 male and 186 female, 41.6% have high school degree, 19.3% have bachelor’s degree and 2.2% have master or Ph. D. degree. The mean age of the respondents was 47 years. The 58% of the participant agreed that they might develop reduce flow to their feet. half of the participant were not aware that smoking can reduce blood flow in their feet. There were only 2.3% of the respondents attended a class on how to care of the foot. Participants who received information about foot care from a nurse and physician were 23% and 9.2% respectively. The 97.5% of the participant would like to know how to care for their foot. 75.8% of participants walk barefoot and 42.2% use a comfortable coated shoe. Conclusions: Participants have inadequate knowledge, attitude and practice about DFD. providing a structured educational program about diabetic foot care has significant impact on diabetic patient to improve their knowledge and practices and to motivate them to have a positive attitude toward diabetic foot care.